Improved grid map layout by point set matching - Eppstein, David; van Kreveld, Marc; Speckmann, Bettina; Staals, Frank (2013 IEEE Pacific Visualization Symposium (PacificVis), 2013)
Associating the regions of a geographic subdivision with the cells of a grid is a basic operation that is used in various types of maps, like spatially ordered treemaps and OD maps. In these cases the regular shapes of the grid cells allows easy representation of extra information about the regions. The main challenge is to find an association that allows a user to find a region in the grid quickly. We call the representation of a set of regions as a grid a grid map.